The Structural Behavior of China-US Trade Flows - Yin-Wong Cheung; Menzie D. Chinn; Xingwang Qian (Center for Economic Studies and ifo Institute (CESifo), 2014)
We examine Chinese-US trade flows over the 1994-2012 period, and find that, in line with the conventional wisdom, the value of China's exports to the US responds negatively to real renminbi (RMB) appreciation, while import responds positively. Further, the combined empirical price effects on exports and imports imply an increase in the real value of the RMB will reduce China's trade balance. The use of alternative exchange rate measures and data on different trade classifications yields additional insights. Firms more subject to market forces exhibit greater price sensitivity. The price elasticity is larger for ordinary exports than for processing exports. Finally, accounting for endogeneity and measurement error matters. Hence, the purging the real exchange rate of the portion responding to policy, or using the deviation of the real exchange rate from the equilibrium level yields a stronger measured effect than when using the unadjusted bilateral exchange rate.
Keywords: F12; F41; 330; import; export; elasticity; real exchange rate; processing trade